Yearbook of International Humanitarian Law Volume 19, 2016 (Yearbook of International Humanitarian Law,, 2018)
The general theme of this volume of the Yearbook of International Humanitarian Law is armed groups and the challenges arising from the participation of such groups in contemporary armed conflicts. It is elaborated upon in several chapters, addressing the organisation criterion, respect for and compliance with international humanitarian law and international human rights law, targeted sanctions and accountability issues, among other things. Besides these chapters that can be connected to the general theme, the book also contains a chapter dedicated to the 'knock on the roof ' practice, a Year in Review, describing the most important events and legal developments that took place in 2016, as well as the final report from the ILA Study Group 'The Conduct of Hostilities Under International Humanitarian Law - Challenges of 21st Century Warfare'. The Yearbook of International Humanitarian Law is the world's only annual publication devoted to the study of the laws governing armed conflict. It provides a truly international forum for high-quality, peer-reviewed academic articles focusing on this crucial branch of international law. Distinguished by contemporary relevance, the Yearbook of International Humanitarian Law bridges the gap between theory and practice and serves as a useful reference tool for scholars, practitioners, military personnel, civil servants, diplomats, human rights workers and students.